Acute lymphoblastic leukaemia. Issue 10230 (4th April 2020) - Malard, Florent; Mohty, Mohamad
Summary: Acute lymphoblastic leukaemia develops in both children and adults, with a peak incidence between 1 year and 4 years. Most acute lymphoblastic leukaemia arises in healthy individuals, and predisposing factors such as inherited genetic susceptibility or environmental exposure have been identified in only a few patients. It is characterised by chromosomal abnormalities and genetic alterations involved in differentiation and proliferation of lymphoid precursor cells. Along with response to treatment, these abnormalities are important prognostic factors. Disease-risk stratification and the development of intensified chemotherapy protocols substantially improves the outcome of patients with acute lymphoblastic leukaemia, particularly in children (1–14 years), but also in adolescents and young adults (15–39 years). However, the outcome of older adults (≥40 years) and patients with relapsed or refractory acute lymphoblastic leukaemia remains poor. New immunotherapeutic strategies, such as monoclonal antibodies and chimeric antigen receptor (CAR) T cells, are being developed and over the next few years could change the options for acute lymphoblastic leukaemia treatment.